2005 IEEE International Conference on Application-Specific Systems, Architecture Processors (ASAP'05)
DOI: 10.1109/asap.2005.52
|View full text |Cite
|
Sign up to set email alerts
|

Power Breakdown Analysis for a Heterogeneous NoC Platform Running a Video Application

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In other studies, it has been observed that in Motorola's M.CORE architecture, the register file contributes up to 42% of data path power dissipation and 16% of the total power consumption, and in Blackfin processor [25] the register file, per se, consumes 20% of the total processor core power consumption. In a Network-on-Chip (NOC) platform it has been observed that register file power consumption can reach to almost 37% of the total system while executing multimedia applications [23]. Even on the more recent processor microarchitecture, the 32 nm Westmere (WSM) core [45], which is used on mobile, desktop and servers, register files contribute to 30% of both dynamic and leakage power dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, it has been observed that in Motorola's M.CORE architecture, the register file contributes up to 42% of data path power dissipation and 16% of the total power consumption, and in Blackfin processor [25] the register file, per se, consumes 20% of the total processor core power consumption. In a Network-on-Chip (NOC) platform it has been observed that register file power consumption can reach to almost 37% of the total system while executing multimedia applications [23]. Even on the more recent processor microarchitecture, the 32 nm Westmere (WSM) core [45], which is used on mobile, desktop and servers, register files contribute to 30% of both dynamic and leakage power dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very recently it has been found that in new proposed embedded platforms with several processing elements, the shared register file plays a very important role as part of the memory subsystem and it can heavily affect the cycle time and consumes a very significant portion of the aforementioned percentage of the total energy consumed by the memory hierarchy [4]. Furthermore, it has become one of the critical processor hot-spots, specially for VLIW architectures, as [8] have shown. The main reasons are similar to those found in other layers of the memory subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very recently it has been found that in new proposed embedded platforms with several processing elements, the shared register file plays a very important role as part of the memory subsystem and it can heavily affect the cycle time and consumes a very significant portion of the aforementioned percentage of the total energy consumed by the memory hierarchy (Texas Instruments, 2004). Furthermore, it has become one of the critical processor hotspots, especially for VLIW architectures, as Lambrechts et al (2005) have shown. The main reasons are similar to those found in other layers of the memory subsystem.…”
Section: Introductionmentioning
confidence: 99%